Rapid CO2 permeation across biological membranes: implications for CO2 venting from tissue. - Hulikova, A; Swietach, P (FASEB, 2014)
The degree to which cell membranes are barriers to CO2 transport remains controversial. Proteins, such as aquaporins and Rh complex, have been proposed to facilitate CO2 transport, implying that the nonchannel component of membranes must have greatly reduced CO2 permeability. To determine whether membrane CO2 permeation is rate limiting for gas transport, the spread of CO2 across multicellular tissue growths (spheroids) was measured using intracellular pH as a spatial readout. Colorectal HCT116 cells have basal water and NH3 permeability, indicating the functional absence of aquaporins and gas channels. However, CO2 diffusivity in HCT116 spheroids was only 24 ± 4% lower than in pure water, which can be accounted for fully by volume exclusion due to proteins. Diffusivity was unaffected by blockers of aquaporins and Rh complex (Hg(2+), p-chloromercuribenzoic acid, and 4,4'-diisothiocyano-2,2'-stilbene-disulfonic acid) but decreased under hypertonic conditions (by addition of 300 mOsm mannitol), which increases intracellular protein crowding. Similar CO2 diffusivity was measured in spheroids of T47D breast cells (basal water permeability) and NHDF-Ad fibroblasts (aquaporin-facilitated water permeability). In contrast, diffusivity of NH3, a smaller but less lipophilic gas, was considerably slower than in pure water, as expected from rate-limiting membrane permeation. In conclusion, membranes, even in the functional absence of proposed gas channels, do not restrict CO2 venting from tissue growths.-Hulikova, A., Swietach, P. Rapid CO2 permeation across biological membranes: implications for CO2 venting from tissue.